Kausalitas Sumber Daya Manusia, Urbanisasi Dan Modal Manusia di Indonesia - Mutiara Idris; Mike Triani (Universitas Negeri Padang, 2023)
This study aims to test hypotheses and interpret each research variable by performing statistical analysis. The variables used in this study are Natural Resources (SDA), Urbanization and Indonesian Human Capital. The technique used in this research is to use the Vector Autoregression (VAR) model technique. The VAR model does not differentiate between exogenous and endogenous variables. All variables in VAR are endogenous variables so that each equation has the same number of regressions. Based on the analysis and discussion described in the previous chapter, it can be said that: 1) The results in this study indicate that there is no reciprocal relationship between urbanization and natural resources in Indonesia. 2) The results in this test show that there is no reciprocal relationship between Natural Resources (SDA) and Human Capital. However, there is only a unidirectional relationship between Human Capital and Natural Resources. 3) The results in this study indicate that there is no reciprocal relationship between urbanization and human capital in Indonesia.